Peculiarities in the hypotensive effects of parathiazine derivatives 2987 RP and 3277 RP (Revista Española de Fisiología, 1951)
The hypotensor effect of 2987 R. P. and of 3277 R. P. is studied comparativel when these medicaments are injected into the saphenous vein and internal carotid and also when the injectiou is rapid or slow (during 5 minutes).R. P. 3277 produces initial hypotension when injected rapidly into the saphenous vein at a dosis of 250 y per kg. weight and into the internal carotid at a dosis of 500 y.R. P. produces the same effects, but the dosis being 500 and 250 y per kg. respectively.To initiate the same hypotension by slow injection of R. P. 3277 into the saphenous vein, four times the quantity is required than in rapid in jection. Slow injection into the internal carotid at the same concentrarion requires eight times the quantity.2987 injected slowly requires the same effect three times the quantity for the saphenous vein and forty times the quantity for the internal carotid than in rapid injection.The authors suppose that the cerebral substance retains or inactivates quantities of 2987 R. P. eight times larger than of R. P. 3277 in spite of the scarce structural difference between both, That add commentaries upon the possible mechanism of the hypotension provoked by these sustances.